Imaging multiphoton ionization dynamics of CH3I at a high repetition rate XUV free-electron laser. (18th December 2020) - Cheng, Yu-Chen; Oostenrijk, Bart; Lahl, Jan; Maclot, Sylvain; Augustin, Sven; Schmid, Georg; Schnorr, Kirsten; Meister, Severin; Rompotis, Dimitrios; Manschwetus, Bastian; Redlin, Harald; Bomme, Cédric; et al.
Abstract: XUV multiphoton ionization of molecules is commonly used in free-electron laser experiments to study charge transfer dynamics. However, molecular dissociation and electron dynamics, such as multiple photon absorption, Auger decay, and charge transfer, often happen on competing time scales, and the contributions of individual processes can be difficult to unravel. We experimentally investigate the Coulomb explosion dynamics of methyl iodide upon core–hole ionization of the shallow inner-shell of iodine (4d) and classically simulate the fragmentation by phenomenologically introducing ionization dynamics and charge transfer. Under our experimental conditions with medium fluence and relatively long XUV pulses (∼75 fs), we find that fast Auger decay prior to charge transfer significantly contributes to the charging mechanism, leading to a yield enhancement of higher carbon charge states upon molecular dissociation. Furthermore, we argue for the existence of another charging mechanism for the weak fragmentation channels leading to triply charged carbon atoms. This study shows that classical simulations can be a useful tool to guide the quantum mechanical description of the femtosecond dynamics upon multiphoton absorption in molecular systems.